2009
DOI: 10.2146/ajhp080118
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence among three methods of administering pantoprazole granules in healthy subjects

Abstract: Three methods of administering pantoprazole delayed-release granules for oral suspension-with apple juice orally, with applesauce orally, and with apple juice through a nasogastric tube--were bioequivalent in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…While pantoprazole tablets need to be ingested whole, granules can be opened; this provides a convenient alternative for children or patients with dysphagia [56]. In a randomized, open-label study of 25 healthy adults, Tammara et al [62] compared two methods of intake of 40 mg pantoprazole granules: with 5 mL (one teaspoon) of applesauce or with 5 mL of apple juice. Both administration methods resulted in comparable AUC and C max values and hence can be considered bioequivalent.…”
Section: Administration Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…While pantoprazole tablets need to be ingested whole, granules can be opened; this provides a convenient alternative for children or patients with dysphagia [56]. In a randomized, open-label study of 25 healthy adults, Tammara et al [62] compared two methods of intake of 40 mg pantoprazole granules: with 5 mL (one teaspoon) of applesauce or with 5 mL of apple juice. Both administration methods resulted in comparable AUC and C max values and hence can be considered bioequivalent.…”
Section: Administration Modesmentioning
confidence: 99%
“…We are convinced that knowledge on this subject is vital to professionally educate patients with the aim to improve their compliance and increase the effectiveness of PPI therapy. -should be taken 60 min before a meal [40] -should be placed on the tongue to disintegrate and swallowed, with or without water [40] DR capsules ↓ AUC (by 35-38%) [34], ↓ C max (by 24-40% and 58-63%, depending on the study) [36,38], ↑ t max (by 2 h) [36] -should be taken 60 min before a meal [33] -should be swallowed whole or with content mixed with 15 mL of applesauce [33] DR granules for oral suspension no studies found -should be taken 60 min before a meal [33] -should be mixed with 5-15 mL of water [33] DR tablets no significant changes in AUC and C max , ↑ t max (by 1.3 h) [41] -can be taken with or without food [41] -should be swallowed whole with water [41] -can be taken with or without food [56,59] -should be swallowed whole with water [56,59] -preferably should be administered in the morning [61] DR granules for oral suspension ↓ AUC (by 29%), ↓ C max (by 51%), ↑ t max (by 2 h) [56] -should be taken 30 min before a meal [56] -content should be sprinkled into 5 mL of applesauce/apple juice [56,62] -do not mix with water or other liquids or food [56] Rabeprazole DR capsules ↓ AUC (by 27%), ↓ C max (by 55%), ↑ t max (by 2 h) [65] -should be taken 30 min before a meal [63] -content should be sprinkled onto a small amount of applesauce/apple juice/yoghurt/fruit or vegetable-based baby food/infant formula/pediatric electrolyte solution [63,65] -can be administered both in the morning or in the evening [67] -evening intake can be beneficial for patients with nocturnal acid breakthrough or nocturnal reflux [66] DR tablets no significant changes in AUC and C max , ↑ t max (by 2.5 h) [42] no significant changes in median intragastric pH [23,24] -can be taken with or with...…”
mentioning
confidence: 99%
“…granule formulation has been developed, to facilitate ease of administration. Similar enteric-coated granules for pantoprazole, [8][9][10] lansoprazole, [11][12][13][14][15] omeprazole, 16,17 and esomeprazole [18][19][20] are available in some countries. Enteric-coated granules have several advantages over enteric-coated tablets, including rapid emptying in the small intestine; faster drug dissolution and absorption; and quicker onset of action.…”
mentioning
confidence: 99%